IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH TERHADAP KUALITAS SARANA DAN PRASARANA DI SEKOLAH DASAR ISLAM AS-SHOFA PEKANBARU - Budiarti, Erna; Hendri Marhadi; Mustafa, Nur (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of School-Based Management (SBM) on the quality of facilities and infrastructure at As-Shofa Islamic Elementary School, Pekanbaru. The research approach uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of SBM has a positive impact on improving the quality of facilities and infrastructure at As-Shofa Islamic Elementary School, Pekanbaru. The implementation of SBM is carried out in stages, namely budget planning, school committee participation, and evaluation of infrastructure maintenance. Improvements in facilities and infrastructure can be seen in the renovation of classrooms, library development, improvements to sanitation facilities and places of worship. The results of this study emphasize that school autonomy in resource management contributes to the quality of school facilities and infrastructure at As-Shofa Islamic Elementary School, Pekanbaru..